Implementing ABC in the telecommunications sector: a case study - Major, M. (Journal of Telecommunications System and Management, 2014)
Profound changes have affected the European telecommunications sector in the last 15 years. With its liberalization at the end of 1990s many telecommunications companies, such as ‘International Telecom’ had to adopt advanced managerial accounting systems that could provide them with detailed and accurate cost accounting information. To this respect Activity-based Costing revealed crucial to aid International Telecom to face fierce competition coming out from the new operators that came into market and to respond to regulatory demands.